PELAKSANAAN CONTRACT RATE ANTARA HOTEL DENGAN PERUSAHAAN BIRO PERJALANAN WISATA - , BENI BINTORO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research includes empirical legal research. These researchâs data in the form of primary data and secondary data. Primary data was collected through a technique carried out in-depth interviews, secondary data collected by the technique of study of documents. Analysis technique used is a qualitative analysis. Presentation of data is done descriptively. This research aims to determine the current contract rate binding, between hotel with Travel Bureau Company, and the factors that led to the cancellation of the booking reservation order issued by the Travel Agency to the hotel is often not resolved through legal side. This research also aimed to find out the dilemma faced by each party in the event of default in the form of cancellation of booking reservation order. This research concluded that the agreement is binding on both parties in the implementation, is when the contract rate whose provided by the hotel was signed by an authorized representative of the Travel Agency and has been welcomed back to the hotel. Cancellation of booking reservation order issued by the Travel Agency to the hotel is often not resolved through legal side, because the booking reservation order is still limited to ordering only, during the performance has not occurred over the use of services and service products from the hotel. The dilemma faced in the event of default in the form of cancellation of booking reservation order is related to the bargaining power and highly depends on the situation and condition of each party. Travel Agency that has a common market could immediately cease all promotional activities and sales of the hotel, while for the hotel usually see from the contributions, both for rooms and events are regular contributed.